A multidimensional index to measure energy poverty: the Polish case. Issue 2 (1st February 2020) - Sokołowski, Jakub; Lewandowski, Piotr; Kiełczewska, Aneta; Bouzarovski, Stefan
ABSTRACT: Energy poverty is generally caused by having a low income, facing high energy costs, and living in a home with low energy efficiency. Various indicators capture these facets, but there is no consensus which is the best one, or how to combine them. To this aim, we create a multidimensional index that accounts for five dimensions of energy deprivation: two objective indicators of "low income, high costs, " and "high actual cost, " as well as three subjective indicators of "not warm enough home, " "housing faults, " and "bills difficulties." We define households as poor if at least two forms of deprivation are present. We apply our measure to Poland. In 2017, 10% of households in Poland suffered from multidimensional energy poverty. Households living in buildings built before 1946, households living in rural areas, and households that were dependent on retirement and disability pensions were at the highest risk of multidimensional energy poverty.